Executive Board Report to the IMFC on Reform of Fund Governance. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper responds to the request in the April 2009 IMFC communique for the Executive Board to report on governance reform. The current crisis has shown that the Fund's decision-making structures can deliver the kind of innovative and rapid responses the membership needs and expects. Even so, there is an undercurrent of doubt about the future, reflecting the perception that much of the recent responsiveness has been driven by outside forces (e.g., the G-20) and that, once the crisis fades, old dissatisfactions with vote, voice and process will resurface to undermine the political backing that has been key to the Fund's renewal. Hence, the IMFC's interest in reforms to underpin the institution's legitimacy and effectiveness is important and timely. This report focuses on five areas: fair quota share; high-level engagement; effective decision-making and representation at the Executive Board; open selection of management (and, more broadly, staff diversity); and updating of the Fund's mandate.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Fund Staff; Fund; IMF Reform; IMF; PP; United States